Scanning electron microscopic evaluation of the root apex of mandibular premolars. - Sant'Anna-Júnior, Arnaldo; Duarte, Marco A H; Guerreiro-Tanomaru, Juliane M; Tanomaru-Filho, Mário (My University, 2010)
This aim of this study was to evaluate the root apex of mandibular premolars regarding the presence of main and accessory foramina. The root apexes from fifty extracted mandibular single-rooted premolars were examined by scanning electron microscopy (SEM). The apical openings had their diameter measured and were identified as main or accessory foramina. Double blinded and calibrated examiners analyzed the SEM photographs and classified the premolar roots into three types, based on the presence and size of the apical openings. Type I: roots with a single main apical foramen and no accessory foramina; type II: roots with a main foramen and one or more accessory foramina; type III: roots with accessory foramina only. For the first premolar, 16 roots were classified as type I (48.48%), 4 as type II (12.12%) and 13 as type III (39.40%). For the second premolars, 10 roots were classified as type I (58.83%), 3 as type II (17.65%) and 4 as type III (23.52%). The high incidence of roots with accessory foramina only (type III), mainly in the first premolar, warns of the need for caution during working length determination and apical debridement.
Keywords: human; mandible; premolar tooth; scanning electron microscopy; tooth root; ultrastructure; Bicuspid; Humans; Mandible; Microscopy, Electron, Scanning; Tooth Apex